1997
DOI: 10.1136/gut.41.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal tone in patients with achalasia

Abstract: Background-The diagnosis and classification of oesophageal motility disorders is currently based on assessment of the phasic contractile activity of the oesophagus. Tonic muscular contraction of the oesophageal body (oesophageal tone) has not been well characterised. Aim-To quantify oesophageal tonic activity in healthy subjects and in patients with achalasia. Patients-Oesophageal tone was measured in 14 patients with untreated achalasia and in 14 healthy subjects. In eight patients with achalasia, oesophageal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
3
25
0
2
Order By: Relevance
“…This finding is similar to that reported in preoperative achalasia patients by Gonzalez et al (8). One lingering question in that study is whether the observed difference in compliance was the result of the pathophysiology of achalasia itself or if it was a byproduct of the esophageal dilatation in the study population.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding is similar to that reported in preoperative achalasia patients by Gonzalez et al (8). One lingering question in that study is whether the observed difference in compliance was the result of the pathophysiology of achalasia itself or if it was a byproduct of the esophageal dilatation in the study population.…”
Section: Discussionsupporting
confidence: 78%
“…The barostat has been effectively used to measure esophageal tone and compliance, as it allows definition of pressure and volume relationships (14). A previous study by Gonzalez et al (8,11) using a barostat apparatus demonstrated increased esophageal compliance in untreated achalasia patients.…”
mentioning
confidence: 99%
“…A manutenção desta inervação com prejuízo de inervação inibitória provocaria aumento da amplitude. Associada à hipocontratilidade, os pacientes com acalásia (13) e com doença de Chagas (8) têm complacência da musculatura do esôfago aumentada, o que significa menor aumento da tensão quando da distensão da parede do órgão.…”
Section: Resultsunclassified
“…3,18 Besides, many achalasia patients, especially those who are older have an altered vagal afferent response leading to a diminished perception of pain. 19,20 In order to detect inflammation, surveillance endoscopy with adequate biopsy sampling is necessary. The interval between the surveillance endoscopies needs further investigation and this may be dependent on the level of inflammation.…”
Section: Discussionmentioning
confidence: 99%